Pemberdayaan Guru Sebagai Penguatan Keterampilan Profesional Dalam Program Pembuatan Modul Proyek Berbasis Kearifan Lokal Melayu Siak - Alexander Alim, Jesi; Hermita, Neni; Putra, Zetra; Erlisnawati, Erlisnawati; Puspitasari, Enda; Sulastio, Agus (Journal of Community Engagement Research for Sustainability, 2024)
Strengthening projectPancasila student profile is a project-based co-curricular activity designed to strengthen efforts to achieve competency and character in accordance withPancasila student profile which is made based on Graduate Competency Standards. One of the themes in the P5 Project is local wisdom in the local area.This theme was chosen in order to build curiosity and inquiry skills through exploration of the culture and local wisdom of the surrounding community or the local wisdom of each school in the area.The problems faced by teachers at SDN 002 Koto Baru are as follows; 1) Lack of knowledge about the project to strengthen the profile of Pancasila students; 2) Lack of training provided by the relevant agencies in implementing and preparing the Project for Strengthening the Pancasila Student Profile, especially regarding the theme of local wisdom; and 3) Teachers do not understand the dimensions, elements, sub-elements and objectives of the Pancasila Student Profile that they want to implement in schools. The training carried out can provide teachers with an understanding of the dimensions, elements and subelements of the Pancila student profile strengthening project. Understanding this can guide teachers in compiling project modules in accordance with local wisdom. Teachers can arrange project modules according to student phases which can be adjusted to the achievement of student characteristics in the class